2013
DOI: 10.1155/2013/469516
|View full text |Cite
|
Sign up to set email alerts
|

A Case of an Undifferentiated Squamous Cell Carcinoma Arising from an Epidermal Cyst

Abstract: An epidermal cyst is a common benign subcutaneous tumor and rarely develops malignancy. We report a case of an undifferentiated cutaneous squamous cell carcinoma (SCC) that arose from an epidermal cyst on the left side of the neck. The epidermal cyst had rapidly increased in size and presented cauliflower-like tumor. Histological study revealed undifferentiated squamous cell carcinoma that was arising from the epidermal cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In a series of 94 cases of SqCC arising in EC reported, the most common site were head and neck (55%) followed by lower limb (13%), trunk (13%), perineum (8%) and upper limb (6%) with a slightly males' predominance (65%) [1] . Another review of 19 cases of SqCC arising in EC showed that majority of those cases were in males and the age ranged from 20 to 80 years old with mean age of 43.2 years [13] . However, previous reports of three cases of EC originating form urinary bladder revealed no malignant transformation ( Table 1 ) but chance of malignant transformation in ECs are always possible.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 94 cases of SqCC arising in EC reported, the most common site were head and neck (55%) followed by lower limb (13%), trunk (13%), perineum (8%) and upper limb (6%) with a slightly males' predominance (65%) [1] . Another review of 19 cases of SqCC arising in EC showed that majority of those cases were in males and the age ranged from 20 to 80 years old with mean age of 43.2 years [13] . However, previous reports of three cases of EC originating form urinary bladder revealed no malignant transformation ( Table 1 ) but chance of malignant transformation in ECs are always possible.…”
Section: Discussionmentioning
confidence: 99%
“…The blamed predisposing factors include chronic history, trauma, recurrent infection, chronic sunlight exposure [29,31], advanced age, skin that is sensitive to ultraviolet radiation, and immunosuppression [32]. Furthermore, chronic inflammation and irritation is classically described to be associated with malignant transformation in lesions behaving similarly to the epidermal cyst, such as pilonidal sinus, hidradenitis suppurativa and chronic osteomyelitis [33].…”
Section: Discussionmentioning
confidence: 99%
“…These signs and symptoms may include the cyst changing into a firmer mass, pain, discharge, inflammation, ulceration, bleeding, rapid increase in size, inflammation or infection not responding to conservative treatment. Such findings may alert the clinician to excise the lump and examine it [7,31,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant transformation is characterized by a long duration: the duration to malignant changes of lesions ranged from 2 to 480 months (mean, 101 months) [3–5] . The mechanism underlying malignant transformation in an epidermal cyst is not clear [6,7] . However, chronic irritation and actinic damage have been proposed as contributing factors.…”
Section: Discussionmentioning
confidence: 99%